2021
DOI: 10.1038/s41598-021-93076-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, risk factors, and outcomes of hospital readmissions of COVID-19 patients

Abstract: To determine the proportion of patients with COVID-19 who were readmitted to the hospital and the most common causes and the factors associated with readmission. Multicenter nationwide cohort study in Spain. Patients included in the study were admitted to 147 hospitals from March 1 to April 30, 2020. Readmission was defined as a new hospital admission during the 30 days after discharge. Emergency department visits after discharge were not considered readmission. During the study period 8392 patients were admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 34 publications
(47 reference statements)
2
26
2
7
Order By: Relevance
“…Positive relationships between age and comorbidities and these outcomes have been observed elsewhere. 28,32,40,41 Meanwhile, differences with respect to gender (in this study's case both outcomes were lower for females versus males) tend to have been absent. 29,30,32,41 We found shorter lengths of stay and lower rates of readmissions for patients belonging to specific ethnic groups with respect to White patients (this was the case for patients belonging to Black ethnic groups for both outcomes, and also Asian, Mixed and 'Other' ethnic groups for length of stay).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Positive relationships between age and comorbidities and these outcomes have been observed elsewhere. 28,32,40,41 Meanwhile, differences with respect to gender (in this study's case both outcomes were lower for females versus males) tend to have been absent. 29,30,32,41 We found shorter lengths of stay and lower rates of readmissions for patients belonging to specific ethnic groups with respect to White patients (this was the case for patients belonging to Black ethnic groups for both outcomes, and also Asian, Mixed and 'Other' ethnic groups for length of stay).…”
Section: Discussioncontrasting
confidence: 50%
“…In our analyses we included a range of factors likely to be associated with LOS and rates of readmissions for COVID-19 patients; [28][29][30][31][32][33] see Table 2. Time period categories were included to take account of fluctuating baseline LOS and rates of readmissions over the analysis period.…”
Section: Variablesmentioning
confidence: 99%
“…1 ). Eventually, 36 studies were included in the present systematic review and 28 were incorporated in the meta-analysis [ 7 , 9 , 11 , [13] , [14] , [15] , [16] , 19 , 20 , 23 , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ]. Overall, 28 articles were included in phase 1 to determine risk factors and outcome of readmitted COVID-19 patients, and 19 articles were included in phase 2 to determine the cause of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…While Joen et al, in their study of 7590 patients, showed that the risk of hospital readmissions increases to up to five times with increasing Charlson comorbidity index [18]. Also, Ramos-Martínez et al showed that the presence of underlying respiratory diseases is a risk factor for hospital readmission, but there was no relationship between cardiovascular and kidney diseases and hospital readmissions [ 81 ]. Therefore, there seems to be a potential relationship between post-discharge of COVID-19 patients and underlying disease.…”
Section: Discussionmentioning
confidence: 99%